Implementing Social Media as Product Marketing Tools for SMEs in Society 5.0 Era (Case: Regency of Gowa) - Wahid (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to explore the potential of social media marketing (SMM) in boosting the performance of small and medium-sized enterprises (SMEs) in various food court areas. The study utilizes qualitative research methodology, collecting data through interviews with SME owners who operate in different locations. The findings indicate that while social media offers numerous benefits for marketing, many SME owners face challenges in utilizing it effectively. The respondents emphasize the need for training and development programs to enhance their digital literacy skills and enable them to leverage modern marketing platforms. The study highlights the importance of government support, educational institutions, and training centers in providing digital literacy education to SME owners.